Riding the decarbonisation wave: BHP and its LNG-fuelled vessels - BHATTACHARYA, Shantanu (Institutional Knowledge at Singapore Management University, 2023)
BHP, the Australian mining company that also diversified into ship chartering, has an important mission statement: “BHP’s purpose is to bring people and resources together to build a better world.” Rashpal Bhatti (Bhatti) Vice President of BHP’s Maritime and Supply Chain Excellence (MSCE) arm endeavoured to bring this purpose to life. The case discusses BHP’s efforts to reduce emissions from its chartering business by transitioning from pollutive conventional fuels to alternative fuels. Maritime transport was the backbone of the global economy. It accounted for 75% of global freight activity, with nearly 80% of globally transported goods being transported by sea, and yet it utilised only one-fifth of the energy or 225 million tonnes of oil equivalent. This made it economical to transport large volumes and weights across vast distances which led to maritime trade doubling between 1990 and 2020. Unfortunately, as maritime trade grew, so did the demand for energy-dense, inexpensive, highly pollutive fossil fuels. To reduce emissions, many in the maritime ecosystem, including BHP, explored the use of alternative fuels. Recognising that the use of alternative fuels involved convincing multiple stakeholders, first, Bhatti secured buy-in from his colleagues and team. Then, the team measured ship emissions and did not charter ships that had poor emission ratings. Next, their research found that Liquified Natural Gas (LNG) produced 30% emission abatements and was the most feasible. Finally, BHP ran tenders for LNG-fuelled ships and for LNG bunker fuel supply. The efforts paid off, and in February 2022, Mt. Tourmaline was delivered to Singapore’s Jurong Port for its first LNG bunkering. Bhatti realised the entire endeavour was successful not only because of LNG fuel innovations but also due to the efforts put forward by stakeholders in the maritime industry, such as vessel owners, regulatory authorities, ship charterers and fuel suppliers. While analysing this case, students will understand more about the importance of steward leadership, decarbonisation in the maritime sector, the benefits of an ecosystem partnership, the importance of aligning organisational purpose with operations, and the role of influence and persuasion when securing buy-in.